Thermal Performance Analysis and Optimization of The Primary Heat Exchanger of The Airbus A320 - Rahmad; Ivan Yosia Adiputra; Djoko Setyanto (Fakultas Teknik Universitas Pancasila, 2026)
The Environmental Control System of the Airbus A320 utilizes a Primary Heat Exchanger to cool bleed air before to its entry into the Air Cycle Machine. Despite the significance of this component for optimal system functionality, research integrating operational data, thermodynamic modeling, and heat transfer studies to enhance its performance in commercial aviation remains sparse. This study investigates the thermal performance of the primary heat exchanger and develops a prediction model based on data gathered from an Airbus A320-214 during routine maintenance operations. The study encompassed 15 unique test situations, differing in bleed air temperature, pressure, and mass flow ratios. The results indicate that the heat exchanger attains a thermal effectiveness of 0.68 to 0.74, with an average heat transfer rate of 48.2 to 62.3 kJ/s, and temperature reductions of 45.2 to 52.8°C. The prediction model utilizing the ε-NTU approach exhibited significant accuracy. Subsequent investigation indicated that the mass flow ratio significantly influences thermal efficacy. Particle Swarm Optimization enhanced the efficacy by as much as 8.5%. The results provide practical criteria for predictive maintenance, facilitating effective Maintenance, Repair, and Overhaul choices in commercial aircraft operations.